A Regional University in the Conditions of the Transition to Digital Technologies: Trends, Opportuni-ties and Prospects for Managing Research Activities - V. Petruk, Galina (2020)
Speeding up in the digitalization of the country's economy has a positive effect on the economic development of the regions, but this requires not only legislative initiatives, but also their scientific justification. The conceptual apparatus for managing the research activities of a regional university in the context of the transition to digital technologies was developed in the paper. It has been proven that in the new economy, universities make a significant contribution to the development of innovation and economic growth.